2022
DOI: 10.1136/bmjopen-2021-057765
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of five nutritional screening tools in Chinese patients undergoing colorectal cancer surgery: a cross-sectional study

Abstract: ObjectivesTo identify the most appropriate nutritional risk screening tool for patients undergoing colorectal cancer surgery, five nutritional screening tools, including the Nutritional Risk Screening 2002 (NRS 2002), Short Form of Mini Nutritional Assessment (MNA-SF), Malnutrition Universal Screening Tool (MUST), Malnutrition Screening Tool (MST) and Nutritional Risk Index (NRI), were employed to evaluate the nutritional risk at admission and short-term clinical outcome prediction.DesignA cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Due to similar results obtained in patients from the two various departments, the GNRI may have a general application value for nutritional risk screening in elderly surgical patients. Recently, the NRS2002, MNA-SF, Malnutrition Universal Screening Tool (MUST), Malnutrition Screening Tool (MST) and Nutritional Risk Index (NRI) were compared in a Chinese colorectal cancer surgery population (31). Multivariate logistic regression analysis revealed that NRS 2002 ≥ 3 was an independent risk factor for postoperative complications and the strongest predictor of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Due to similar results obtained in patients from the two various departments, the GNRI may have a general application value for nutritional risk screening in elderly surgical patients. Recently, the NRS2002, MNA-SF, Malnutrition Universal Screening Tool (MUST), Malnutrition Screening Tool (MST) and Nutritional Risk Index (NRI) were compared in a Chinese colorectal cancer surgery population (31). Multivariate logistic regression analysis revealed that NRS 2002 ≥ 3 was an independent risk factor for postoperative complications and the strongest predictor of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%